Konsep Falsafah Pendidikan Anak Usia Dini Berbasis Al-Qur’an: Analisis Nilai Tauhid, Tarbiyah, dan Akhlak - Hadi Sumitro, Wiwid (Ar-Raihanah: Jurnal Pendidikan Islam Anak Usia Dini, 2024)
The moral decline among early childhood learners in the digital era demands a reorientation of education based on Qur’anic values. Early childhood education in Islam is not merely a process of knowledge transmission but a holistic formation of personality through the integration of spiritual, moral, and social aspects. This study aims to explore the philosophical concept of Qur’an-based early childhood education by analyzing the core values of tawhid (monotheism), tarbiyah (education), and akhlaq (morality) as the foundation for Islamic character formation. A qualitative-descriptive approach was employed using the thematic (maudhu‘i) method of Qur’anic interpretation focusing on verses such as Luqman [31]:12–19, Al-Isra [17]:23–24, and At-Tahrim [66]:6. The findings reveal that Qur’anic education emphasizes three interrelated dimensions: tawhid as the spiritual foundation, tarbiyah as a comprehensive educational process, and akhlaq as the ultimate moral goal. This framework creates a holistic model that balances intellectual, emotional, spiritual, and social intelligence. The study implies the necessity of integrating Qur’anic values into early childhood education curricula to cultivate ulul albab—intelligent, ethical, and spiritually enlightened individuals